Implementation levels of virtualization and security issues in cloud computing - Banushri, A; R. A. Karthika, Dr (International Journal of Engineering and Technology, 2018)
Cloud is the buzz word in the industry. The initiation of virtualization technology in the infrastructure domain gives us the options to procure the benefits of the cloud deployments. Virtualization is a fast-growing infrastructure in the IT industry. Technology providers and user communities have introduced a new set of terms to describe the technologies and their features for virtualization. Virtualization characterizes the logical vision of data representation. The authority to compute in virtualized environment, storing the data at dissimilar geographies and diverse computing resources. Virtualization technology allows the creation of the virtual versions of hardware, networking resources, Operating systems and storage devices. It supports multiple OS run on single physical machine called host machine and multiple guest application run on single server called host server. Hypervisors assistance in virtualization of hardware. That is, the software interrelates with the physical system, providing virtualized environment to maintain multiple operating system running parallel using one physical server. This paper provides the information about the implementation levels of virtualization, the benefits and security problems of Virtualization in virtualized hardware environment.Â Â Â